A sedução do falso: emergência e significação de falsos perfis nos websites de redes sociais - Pereira, Heloisa Prates (2014)
This research examines the status and the significance of fake profiles created by users inwebsites based on social networks. The main objective of this investigation was to understandhow these profiles generate meanings in technologically mediated communication. It wasconducted through literature review and semiotic analysis. Its foundations were the theories ofdiscurse and cyberculture, on the perspective of Ernesto Laclau, Chantal Mouffe, Slavoj i ek, José Luiz Aidar Prado and Eugênio Trivinho, as long as Mikhail Bakhtin's theory oflanguage and Algirdas J. Greimas's approach on the discursive semiotic. Underpinned by thistheoretical articulation, we understand that there is an hegemonic discurse of cyberculturebuilt from the ideological fantasy that network connections are the technological basis for aworld in wich the constraints to the free flow of significantions will be overcome, turningcompossible all the antagonisms. The analysis bends over a corpus composed of six cases offake profiles created on the most popular social networking sites in Brazil Facebook andTwitter , which were divided into three axes of manifestation: the laughter, the derision andthe reverse. The hypothesis advocated is that the fake profiles of the reverse deconstruct thisfantasy and expose its constitutive lack. The other two types, linked to the axes of thelaughter and the derision, fetishized, occupy the position of nodal points of the discurse. Theyact as dispositives that shoot the subject into the ideological fantasy of cyberculture, seducinghim to seek the satisfaction of his impulses of connection in cyberspace. The profiles of thelaughter and of the derision plug the hole rendered visible by the profiles of the reverse.Within the ambiguity of the concept of "fake", the first profiles overlap the last ones. Thus,the fantasy of plenitude of the hegemonic discurse of ciberculture is restored, reordening thesocial practices in the present by the denegation of its constitutive lack. Since the interactionvia social networking websites and applications has become an unavoidable standard ofbehavioring for nowadays sociability, and that into these digital contexts the fake profilesmultiply themselves, the research aims to contribute to the Communication field and to thecyberculture studies by proposing theoretical advances in understanding this phenomenon ofcontemporary social communication.